Tourism : - Wall, Geoffrey (Pearson / Prentice Hall, 2006)
This new text builds upon the success of the classic Mathieson & Wall original Tourism: economic, physical and social impacts to provide a comprehensive and rigorous examination of the consequences of tourism. The authors address the nature of tourism and tourists and the economic, environmental and social impacts that result from their activities. It provides a unique blend of theoretical principles and practice for a balanced approach to tourism.nbsp;Key featuresnbsp; new approaches to impact assessment are considered as well as a rethinking of tourism impacts nbsp; uses international case studies and models to illustrate key concepts nbsp; wide range of examples from both the developing and developed world nbsp; incorporates the latest insights and literature nbsp; contains new chapters on frameworks for analysis and sustainable developments nbsp; contains an extensive bibliography and subject, place and author indexes to permit easy access to information nbsp;This text will be essential reading to students, academics and practitioners of tourism, leisure, hospitality, geography, management, business studies and the wider social sciences.nbsp;Geoffrey Wall is Professor of Geography at the University of Waterloo, Canada.Alister Mathiesonnbsp; is Dean, School of Hospitality, Recreation and Tourism, Humber Institute of Technology and Advanced Learning, Toronto, Canada.nbsp